Prevalence of morbidity and mortality of diabetes mellitus in a rural community cohort - Sayeed, M Abu; Khanam, Parvin Akter; Banu, Akhter; Ahsan, Khandaker Abul; Haq, Fazlul (IMC Journal of Medical Science, 2021)
Background and objectives: The developing countries are facing the double burden of the communicable (CD) and non-communicable (NCD) diseases. The initiation of primary health care (PHC) adopted in the past century, which included sanitation and immunization, remarkably reduced the load of CDs in the least developing nations. The burden of NCDs remained the same or showed an increasing trend. Of the NCDs, diabetes has become a serious threat to human health and the related morbidity and mortalities are affecting the younger people. As a consequence, the disease complications render huge number of people to disabilities and unusual enormous health expenditures. Very few studies addressed the prevalence of complications among the diabetes patients in a rural community. This study aimed to determine the prevalence of sequels (morbidity and mortality) among the diabetic cases eight years after the initial diagnosis of diabetes in a rural community cohort Subjects and Methods: A rural community survey in 10 villages was conducted in 1993. The survey screened 1319 (797 men, 522 women) for diabetes mellitus (DM) and impaired glucose tolerance (IGT). Those who were diagnosed DM and IGT referred to a referral center (BIRDEM) for registration. A retrospective cohort was designed in 2001. The addresses of the patients were retrieved from the BIRDEM registry. These registered patients, both survivors and non-survivors, were traced in ten villages. The survivors were investigated (anthropometry, glycemia, fundoscopy, urine protein etc.). A verbal autopsy was performed to determine the cause(s) of death in the non-survivors. Results: Of the188 registered cases, 79 were found and located (survivors 43 (54.4%, non-survivors 36 (45.6%). Of the survivors, 44.2% developed complications. The observed complications were sensory neuropathy 16.3%, CAD 9.3%, retinopathy 7% and nephropathy 4.7%. Among the non-survivors, 19.4% were found to have nephropathy leading to end-stage renal disease. Conclusions: The study cohort revealed that more than one-third of the people with diabetes died in less than ten years after being diagnosed. The cohort also revealed that diabetic nephropathy (end-stage renal disease) and dearth of dialysis facilities contributed to early death in the rural community. Among the complications, most frequent incidence was neuropathy and neuro-psychiatric disorders. Ibrahim Med. Coll. J. 2021; 15(1): 31-36